Contributions of livestock-derived foods to nutrient supply under changing demand in low- and middle-income countries - Enahoro, Dolapo K.; Lannerstad, Mats; Pfeifer, Catherine; Domínguez Salas, Paula (Elsevier, 2018)
The potential to use large-scale dietary transformations to meet nutritional needs of the world's poorest populations may have been largely overlooked. A case study is presented of food nutrient supplies in eight selected countries within the context of their growing demand for livestock-derived food (LDF). For almost all the countries and under a range of scenarios of economic and climatic change in 2050, we find that per capita protein supply from LDF will increase relative to that from plant sources. Survey data indicate higher LDF consumption, up to 22%, among children in households that keep livestock compared to others. However, projections that four of the selected countries will import at least 40% of their LDF protein highlight the opportunity to increase livestock sector production and the potential to develop smallholder inclusive policies.